Method for producing modified aluminosilicate, method for producing catalyst comprising modified aluminosilicate, method for producing aromatic polyhydroxy compound using said catalyst, and modified aluminosilicate
By controlling the molar ratio of water to silica and using sol-like silica with acid treatment and transition metals, the method addresses transportation and reactivity challenges in producing aromatic dihydroxy compounds, achieving high selectivity and yield.
Patent Information
- Application Number
- CN202380035284.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-01-17
- Filing Date
- 2023-04-21
- Publication Date
- 2024-12-24
AI Technical Summary
Existing methods for producing aromatic dihydroxy compounds, such as hydroquinone and catechol, face challenges with the formation of solid lumps in gel-like silica intermediates, leading to transportation issues and reduced reactivity, which complicates industrial production and increases costs.
A method involving the use of sol-like silica with controlled molar ratios of water to silica (H2O/SiO2) and subsequent acid treatment, followed by calcination and contact with transition metal compounds, to produce a modified aluminosilicate catalyst that enhances selectivity and yield.
The method efficiently produces aluminosilicate catalysts with high selectivity for aromatic dihydroxy compounds, addressing industrial stability and cost issues by maintaining fluidity and reaction efficiency.
Smart Images

Figure BDA0005093646920000321 
Figure BDA0005093646920000322 
Figure HDA0005093646930000011
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a modified aluminosilicate, a method for producing a catalyst containing the modified aluminosilicate, a method for producing an aromatic dihydroxy compound using the catalyst, and the modified aluminosilicate. Background Art
[0002] Aromatic dihydroxy compounds are important as intermediates or raw materials for various organic synthesis and can be used in the fields of reducing agents, rubber additives, dyes, medicines, pesticides, inhibitors, oxidation inhibitors, etc.
[0003] Aromatic dihydroxy compounds obtained by reacting phenols with hydrogen peroxide are, for example, hydroquinone, catechol, etc. The production ratio of hydroquinone and catechol varies depending on the production method. In recent years, a method for producing hydroquinone with high selectivity has been particularly eagerly awaited from the perspective of the demand balance between hydroquinone and catechol.
[0004] In order to produce aromatic dihydroxy compounds by reacting phenols with hydrogen peroxide, a method using titanosilicate, which is one of crystalline porous silicates, as a catalyst is disclosed (e.g., Patent Document 1, Patent Document 2). In addition, Patent Document 3 discloses titanosilicate obtained by treating acid-treated aluminosilicate with gaseous titanium chloride or titanium alkoxide.
[0005] Patent Document 4 discloses a method for producing titanosilicate by mixing a mold raw material of aluminosilicate, an aluminum source, a titanium source, a silicon source, an iodide, and water to prepare a gel, heating the gel to crystallize it, and then calcining the gel.
[0006] The present inventors disclosed a method for producing aluminosilicate by bringing an aluminosilicate compound into contact with a liquid titanium halide compound (Patent Document 5).
[0007] Prior art literature
[0008] Patent Literature
[0009] Patent Document 1: Japanese Patent No. 4254009
[0010] Patent Document 2: International Patent Publication No. 2015 / 041137
[0011] Patent Document 3: Japanese Patent Application Publication No. 2008-050186
[0012] Patent Document 4: Japanese Patent Application Publication No. 2017-057126
[0013] Patent Document 5: International Patent Publication No. 2019 / 225549 Summary of the invention
[0014] Problems to be solved by the invention
[0015] The aluminum titanosilicate obtained from the above-mentioned Patent Document 5 is suggested to be an excellent catalyst for the production of aromatic dihydroxy compounds. Among them, it is disclosed that the aluminum titanosilicate introduced with a titanium source using titanium tetrachloride provides aromatic dihydroxy compounds with a particularly high selectivity. In addition, according to the X-ray crystal structure analysis (X-ray diffraction (XRD) diagram) of the present inventors, the above-mentioned aluminum titanosilicate is a compound showing a maximum peak at 23 to 24°.
[0016] According to the research of the present inventors, it is known that sometimes lumps of solid matter are produced in the gel-like silica used as an intermediate raw material. From an industrial point of view, the presence of such solid matter may hinder the stable and quantitative transportation of the contents when transported to the reaction device (such as an autoclave) for hydrothermal synthesis in the next process, or reduce the reactivity in the subsequent process because it is a solid. Therefore, from the perspective of stable production, it is sometimes disadvantageous. If the solid matter is crushed, the above-mentioned problem is substantially solved, but in order to carry out the crushing, it sometimes leads to an increase in fixed costs such as the need for special equipment and a reduction in manufacturing speed, and the manufacturing process becomes complicated when industrial production is carried out.
[0017] The present invention aims to provide a method for producing a modified aluminosilicate such as aluminum titanosilicate, which can produce hydroquinones satisfactorily with higher selectivity and high yield, for example, by reacting phenols with hydrogen peroxide, etc., under industrially more favorable conditions than before. In addition, the present invention aims to provide a catalyst capable of stably producing hydroquinones with high selectivity, for example, by reacting phenols with hydrogen peroxide, etc., under industrially more favorable conditions, and a method for producing an aromatic polyhydroxy compound using the catalyst, as well as a modified aluminosilicate.
[0018] Means for solving problems
[0019] The present inventors have studied the above-mentioned subject and found that, by bringing a silicate source such as silica in a sol state containing water into contact with an aluminum source such as zeolite in a sol state and then controlling the molar ratio of water to silica (H2O / SiO2) (hereinafter sometimes referred to as "HMR"), the HMR value has a great influence on the performance of the solid. It was found that by setting a process for controlling the HMR value within a specific range, a suitable aluminosilicate can be efficiently produced even from a sol state having better fluidity than a gel. In addition, it was found that the aluminosilicate can be transformed into a modified aluminosilicate such as aluminum titanosilicate that can produce hydroquinones with an extremely high selectivity after an acid treatment process and a contact treatment process with a transition metal compound such as a titanium compound, thereby completing the present invention.
[0020] That is, the present invention includes the matters described in the following [1] to
[10] .
[0021] [1] A method for producing a modified aluminosilicate, comprising the following steps:
[0022] The first step is to prepare a liquid in which a sol-like silica containing water is brought into contact with a metal compound (AL) containing aluminum and oxygen, thereby obtaining an aluminosilicate having a molar ratio of water to silica (H2O / SiO2: HMR) in the liquid in the range of 0.1 to 8.0;
[0023] The second step is to treat the aluminosilicate obtained in the first step with an acid;
[0024] The third step is to calcine the treated product obtained in the second step at 550° C. to 850° C.; and
[0025] The fourth step is to bring the fired product obtained in the third step into contact with a liquid containing one or more elements selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table, and then dry and perform secondary firing.
[0026] [2] The method for producing a modified aluminosilicate according to [1], wherein the HMR is in the range of 3.0 to 6.6.
[0027] [3] The method for producing a modified aluminosilicate according to [1] or [2], wherein the metal compound (AL) containing aluminum and oxygen is zeolite.
[0028] [4] The method for producing a modified aluminosilicate according to any one of [1] to [3], wherein the first step includes a step of removing a portion of water.
[0029] [5] A method for producing modified aluminosilicate as described in [1], wherein in the first step, after preparing a liquid in which a sol-like silica containing water is brought into contact with a zeolite, a portion of the water in the liquid is removed to obtain an aluminosilicate having a molar ratio of water to silica (H2O / SiO2: HMR) in the range of 0.1 to 8.0.
[0030] [6] A method for producing a catalyst for producing an aromatic polyhydroxy compound, the catalyst comprising the modified aluminosilicate described in any one of [1] to [4].
[0031] [7] A method for producing a catalyst for producing an aromatic polyhydroxy compound, the catalyst comprising the modified aluminosilicate described in [5].
[0032] [8] A method for producing an aromatic polyhydroxy compound, comprising: reacting an aromatic hydroxy compound with hydrogen peroxide in the presence of the catalyst described in [6].
[0033] [9] A method for producing an aromatic polyhydroxy compound, comprising: reacting an aromatic hydroxy compound with hydrogen peroxide in the presence of the catalyst described in [7].
[0034]
[10] A modified aluminosilicate, wherein the ratio (A
[300] / A
[210] ) of the absorbance at 300 nm in the ultraviolet-visible absorption spectrum (A
[300] ) to the absorbance at 210 nm in the ultraviolet-visible absorption spectrum (A
[210] ) is 0.045 or more and 0.070 or less.
[0035] Effects of the Invention
[0036] One of the characteristics of the manufacturing method of the modified aluminosilicate is that even if a sol-like silica obtained by heating a gel-like silica containing water is used, an industrially useful aluminosilicate can be efficiently obtained. Thus, even if the sol-like silica containing water is contacted with a metal compound (AL) containing aluminum and oxygen represented by zeolite (aluminum compound crystal) as an aluminum source, the ratio of water to silica as a part of the raw material is controlled within a specific range to manufacture, and an aluminosilicate suitable for the production of the aluminum titanosilicate described later can be efficiently produced. In addition, the aluminosilicate is preferably an aluminosilicate having a specific structure determined by an X-ray diffraction pattern. In addition, even if the aluminosilicate is contacted with a liquid containing one or more elements selected from the group consisting of the 4th group element and the 5th group element of the periodic table, such as an aqueous solution of a titanium source, under mild conditions, an aluminum titanosilicate used for a catalyst for the manufacture of aromatic polyhydroxy compounds can be obtained. In addition, such an aluminum titanosilicate sometimes shows an ultraviolet-visible spectrum (UV-Vis) that meets specific requirements. Therefore, the present invention has industrial significance. In addition, by using the modified aluminosilicate produced by the above production method, for example, phenols can be reacted with hydrogen peroxide to produce aromatic dihydroxy compounds such as hydroquinone with high selectivity. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a graph showing the X-ray diffraction patterns of the aluminosilicates obtained in Examples 1 to 3 and Comparative Example 1.
[0038] Figure 2 This is a graph showing the X-ray diffraction patterns of the aluminosilicates obtained in Examples 4 to 8. DETAILED DESCRIPTION
[0039] Hereinafter, embodiments of the present invention will be described in detail.
[0040] <Method for producing aluminosilicate>
[0041] The manufacturing method of the modified aluminosilicate of the present invention comprises:
[0042] The first step is to prepare a liquid obtained by contacting a sol-like silica containing water with a metal compound (AL) containing aluminum and oxygen, preferably a zeolite, to obtain an aluminosilicate having a molar ratio of water to silica (H2O / SiO2: HMR) in the range of 0.1 to 8.0;
[0043] The second step is to treat the aluminosilicate obtained in the first step with an acid;
[0044] The third step is to calcine the aluminosilicate obtained in the second step at 550° C. to 850° C.;
[0045] The fourth step is to bring the fired product obtained in the third step into contact with a liquid containing one or more elements selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table, and then dry and perform secondary firing.
[0046] [Colloidal Silica]
[0047] The sol-like silica containing water (hereinafter, the sol-like silica containing water is referred to as "sol-like silica") used in the present invention can use known sol-like silica without limitation. The sol-like silica can be preferably obtained by contacting a nitrogen-containing compound such as a quaternary ammonium salt, a known alkali source, and a silica source such as a commercially available colloidal silica, and then heating and stirring appropriately.
[0048] As the quaternary ammonium salt, specifically, there can be mentioned: a salt containing an ammonium ion (cation) containing 4 moles of substituents such as hydrocarbon groups with 1 to 10 carbon atoms relative to 1 mole of nitrogen atoms, and anions such as halogen ions such as hydroxyl ions, chloride ions, bromide ions, and iodide ions. As the hydrocarbon group, a hydrocarbon group with 1 to 8 carbon atoms is more preferred, 1 to 6 carbon atoms is further preferred, and 1 to 4 carbon atoms is particularly preferred. On the other hand, as anions, hydroxyl ions, bromide ions, and iodide ions are more preferred, and hydroxyl ions are further preferred. As such a quaternary ammonium salt, more specifically, for example, tetrapropylammonium hydroxide, tetrabutylammonium hydroxide, dimethyldipropylammonium hydroxide, tetrapropylammonium bromide, bis-1,6-(tripropylammonium)hexamethylene diiodide, etc. Dimethyldipropylammonium hydroxide is particularly preferred.
[0049] Such quaternary ammonium salts are sometimes referred to as organic structure directing agents, and sometimes have the function of controlling the higher-order structure of silica or aluminosilicate.
[0050] In the present invention, the ratio of the silicon dioxide to the quaternary ammonium salt is preferably in the range of 1.5 to 10 in terms of silicon atom / nitrogen atom molar ratio. A more preferred lower limit of the ratio is 1.7, more preferably 1.9, and particularly preferably 2.0. On the other hand, a more preferred upper limit of the ratio is 9, more preferably 8, and particularly preferably 7.
[0051] When a seed crystal described later is not used, the silicon atom / nitrogen atom molar ratio is preferably slightly higher than the above range in some cases, and its lower limit is preferably 2.5, more preferably 3.0, further preferably 3.6, and particularly preferably 3.7.
[0052] In the present invention, the molar ratio of water to silica in the colloidal silica is preferably a value exceeding 8.0.
[0053] As for the water, as preferred examples, water contained in commercially available colloidal silica, water contained in the organic structure directing agent and alkali source described later, pure water used in combination by additional addition, etc. Of course, as long as it is water, it may be in a form other than the above.
[0054] In addition, the temperature when producing the above-mentioned sol-like silica is preferably set to a relatively high temperature. Such a temperature is preferably 40°C or higher, more preferably 50°C or higher, further preferably 60°C or higher, and particularly preferably 70°C or higher. On the other hand, the upper limit temperature is preferably 100°C, more preferably 95°C, further preferably 92°C, and particularly preferably 90°C.
[0055] Here, the present invention is characterized in that, in the first step, a liquid is prepared after the sol-like silica is brought into contact with the metal compound (AL), and the molar ratio of water to silica (H2O / SiO2: HMR) is controlled in the range of 0.1 to 8.0. As the above-mentioned control method, it is preferred to include a step of removing a portion of water in the liquid containing the sol-like silica and the metal compound (AL).
[0056] The preferred lower limit of the HMR is 1.0, more preferably 2.0, further preferably 3.0, and particularly preferably 3.6. On the other hand, the preferred upper limit of the HMR is 7.5, more preferably 7.0, further preferably 6.6, particularly preferably 6.2, and particularly preferably 5.8. When the HMR is too low, the solid obtained may not be able to obtain sufficient effects in the second step (removing part of the aluminum by acid treatment, etc.) and the third step (introducing the transition metal by contact with a transition metal compound, etc.) described later. If the HMR exceeds 8.0, the aluminosilicate having the above-mentioned suitable structure may not be obtained due to a decrease in the reaction rate, etc.
[0057] Industrially, it is preferred that various processes are implemented using multiple reactors, and the movement of the contents between the reactors is carried out via piping. Therefore, various reactants are preferably in a particulate state with fluidity in addition to liquid phases such as liquid, solution, and slurry. In the past, gel-like silica was used as a raw material in the method of patent document 5, but if sol-like silica can be used as a silica raw material, it is preferred from the above viewpoint.
[0058] On the other hand, it is considered that if such silica is used, the reaction with the metal compound (AL) may become insufficient, and the effect of the structure directing agent and the effect of the seed crystal described later, which are preferably used in combination, may not be obtained. However, the present inventors have found that in the present invention, as described above, by setting the HMR at the stage after the sol-like silica and the metal compound (AL) are brought into contact with each other to satisfy the conditions in a specific range, it is possible to obtain aluminosilicate as a suitable raw material for the catalyst described later.
[0059] It is considered that in the production method for obtaining aluminosilicate having a specific structure as described below, the shape and number of pores of the obtained aluminosilicate are likely to be affected by the difference in the HMR value, and as a result, the reaction state in the second step and the third step described below and the form of the product are affected. Therefore, the present inventors believe that it is important to control within the above-mentioned numerical range.
[0060] The effect of controlling HMR as described above is as described above, and in addition, the second step and the third step may also be greatly affected.
[0061] 〔First process〕
[0062] The first step is a step of preparing a liquid obtained by contacting colloidal silica as a silicon source with the above-mentioned metal compound (AL) as an aluminum source, and manufacturing an aluminosilicate having an HMR in the range of 0.1 to 8.0. As the above-mentioned metal compound (AL), various aluminum oxides, composite metal oxides containing aluminum and other well-known metal oxides can be cited. As a more specific preferred example, aluminosilicates can be cited, and zeolites are particularly preferred. As the zeolite, FAU zeolite and MSE zeolite are preferred, and FAU zeolite is more preferred. At this time, it is preferred to include: a step of contacting aluminosilicate crystals (A) having an MSE type structure with colloidal silica in advance. In addition, aluminum salts such as aluminum hydroxide, sodium aluminate, aluminum nitrate, and aluminum sulfate can also be exemplified.
[0063] The aluminosilicate obtained in the first step and the aluminosilicate crystal (A) are preferably porous. Hereinafter, the crystalline and porous aluminosilicate is simply referred to as crystalline porous aluminosilicate.
[0064] The MSE type aluminosilicate (A) can be considered as a crystal called a "seed crystal" when producing the aluminosilicate described later. By using a crystal having a structure as described above, it is sometimes advantageous to obtain a modified aluminosilicate that is a raw material suitable for a catalyst for producing an aromatic polyhydroxy compound described later. On the other hand, depending on the production conditions, it is sometimes preferable not to use a seed crystal.
[0065] The seed material used in the present invention is not particularly limited as long as it has the above-mentioned structure. As mentioned above, it is preferably a crystalline porous aluminosilicate having an MSE type structure (hereinafter referred to as "MSE skeleton") in the structure code of the International Zeolite Association, and is particularly preferably UZM-35, MCM-68, YNU-3, etc.
[0066] The crystalline porous aluminosilicate having an MSE skeleton has the following three-dimensional pore structure, which has a regularly three-dimensionally bonded part consisting of SiO4 tetrahedrons with oxygen arranged at four vertices with silicon as the center and TiO4 tetrahedrons with titanium arranged instead of the central silicon, and has a 10-membered ring structure formed by 10 units of the tetrahedron and a 12-membered ring structure formed by 12 units of the tetrahedron in an arbitrary proportion.
[0067] The first step of the present invention can be carried out, for example, by the following method: a known silicon source such as known colloidal silica is contacted with the above-mentioned metal compound (AL), preferably an aluminum source such as zeolite, and a quaternary ammonium salt (preferably an organic structure directing agent such as dimethyldipropylammonium hydroxide) and a known alkali source, and stirred and heated. It should be noted that the above-mentioned silicon source, quaternary ammonium salt, and alkali source may include substances derived from the above-mentioned sol.
[0068] As the silica source, a method using gelled silica is known, but as described above, gelled silica is solid, and it is sometimes difficult to obtain the effects in the second and third steps described later from the viewpoint of reaction efficiency, etc. In addition, from the viewpoint of fluidity, it is believed that productivity may be reduced.
[0069] The present invention is characterized in that after contacting the sol-like silica with the above-mentioned metal compound (AL), preferably an aluminum-containing compound such as zeolite to obtain a contact product, the molar ratio (HMR) of water to silica is within a specific range. As described above, the inventors of the present invention have found that if an aluminosilicate obtained through such an HMR state is used, a suitable substance can be obtained when manufacturing modified aluminosilicates and catalysts such as aluminum titanosilicates described later. Any known method can be applied to the method of setting such an HMR range. For example, a method of heating and reducing the pressure to remove water from the above-mentioned contact product can be cited. In addition, a method of removing water by contacting it with a water absorbent can also be exemplified. More specifically, a method of passing the above-mentioned contact product through a fixed bed filled with a water absorbent can be exemplified. Among them, heating, reducing the pressure and a combination of the two are preferred.
[0070] In the present invention, it is preferred that the first step includes a step of removing a portion of water in the liquid.
[0071] It should be noted that the HMR value can be determined by any known method for measuring water content, or it can be calculated based on data related to material balance during the reaction process.
[0072] By providing a step to achieve a specific HMR range under the above-described specific conditions, it is possible to efficiently produce a modified aluminosilicate such as aluminotitanium silicate and an aluminosilicate suitable as a raw material for a catalyst.
[0073] In order to achieve the state of the above-mentioned HMR range, the temperature at the stage of contacting the sol-like silica with the above-mentioned metal compound (AL), preferably zeolite, is preferably the same as the preferred temperature range when the sol-like silica is produced, preferably 40° C. or more, more preferably 50° C. or more, further preferably 60° C. or more, and particularly preferably 70° C. or more. On the other hand, the upper limit temperature is preferably 100° C., more preferably 95° C., further preferably 92° C., and particularly preferably 90° C.
[0074] Next, the contact material of the colloidal silica, the metal compound (AL), preferably zeolite, preferably the seed crystal and the structure directing agent is preferably heated to 140-175°C and maintained for 10-150 hours. The more preferred lower limit of the temperature is 145°C, and more preferably 148°C. In addition, the preferred lower limit is sometimes 155°C, more preferably 157°C, more preferably 159°C, and particularly preferably 160°C. On the other hand, the more preferred upper limit of the temperature is 170°C, more preferably 168°C, and particularly preferably 165°C. If the above conditions are set, it is preferred for manufacturing modified aluminosilicates such as aluminum titanosilicates described later and aluminosilicates as suitable raw materials for catalysts. For example, if the above conditions are set, as also disclosed in the examples, the above conditions tend to be suitable from the viewpoint of increasing the selectivity of the generated compounds. The above temperature range can be applied to both the case where the seed crystals are used and the case where the seed crystals are not used.
[0075] In addition, the preferred lower limit of the above time is 15 hours, and more preferably 20 hours. On the other hand, the preferred upper limit is 140 hours, and more preferably 130 hours. In addition, sometimes it is preferably 68 hours, more preferably 65 hours, and more preferably 60 hours.
[0076] In the present invention, for example, in the method of using the above-mentioned seed crystals, the above-mentioned heating treatment conditions are sometimes preferably carried out at a relatively low temperature. The low temperature preferably refers to 140°C or more and less than 160°C. The preferred lower limit of the temperature is 145°C, and the preferred upper limit is 157°C, and more preferably 155°C. In addition, the preferred lower limit of the above-mentioned heating treatment time is 10 hours, more preferably 20 hours, more preferably 23 hours, particularly preferably 30 hours, and particularly preferably 35 hours. In addition, depending on the stirring efficiency and mixing efficiency of each component caused by stirring conditions, container shape, etc., sometimes a longer time is preferred, for example, the lower limit is 40 hours, more preferably 45 hours, more preferably 50 hours, particularly preferably 55 hours, and particularly preferably 60 hours. On the other hand, the preferred upper limit of the above-mentioned treatment time is 140 hours, more preferably 130 hours. When using the seed crystal in this way, heating at a low temperature is sometimes conducive to obtaining a modified aluminosilicate that satisfies the parameters of the ultraviolet absorption intensity in a special range as described later (for example, a tendency to show excellence from the perspective of reaction yield).
[0077] In this case, the HMR value is preferably 4.0 to 7.5. The lower limit is more preferably 4.5, further preferably 5.0, particularly preferably 5.5, and particularly preferably 5.7. On the other hand, the upper limit is more preferably 7.0, further preferably 6.8.
[0078] In the present invention, for example, in a method without using the above-mentioned seed crystals, the above-mentioned heat treatment conditions are sometimes preferably carried out for a long time at a relatively low temperature. The low temperature preferably refers to 140°C or more and less than 165°C. The preferred lower limit of the temperature is 145°C, the preferred upper limit is 160°C, and more preferably 155°C. In addition, the above-mentioned long time preferably refers to more than 40 hours and less than 150 hours. The more preferred lower limit of the above-mentioned time is 50 hours, further preferably 60 hours, further more preferably 70 hours, particularly preferably 80 hours, and particularly preferably 85 hours. On the other hand, the preferred upper limit is 140 hours, and more preferably 130 hours. In such a method without using seed crystals, by heating at a low temperature for a long time, it is sometimes beneficial to obtain a modified aluminosilicate that satisfies the parameters of the ultraviolet absorption intensity in a special range as described later (for example, a tendency to show excellence from the perspective of reaction yield).
[0079] In this case, the HMR value is preferably 3.0 to 6.0. The lower limit is more preferably 3.5, and further preferably 4.0. On the other hand, the upper limit is more preferably 5.8, and further preferably 5.6.
[0080] When the first step is carried out under the above conditions (for example, with the purpose of emphasizing the reaction yield), there is a tendency to easily produce a modified aluminosilicate having [A300] / [A210] within a specific range as described below. The reason for this tendency is not clear at present, but the present inventors speculate as follows.
[0081] It is believed that if the above conditions are met, the aluminosilicate crystallization is carried out under a relatively mild environment from a state with a high degree of freedom such as a sol to a slightly lower temperature condition, so there is a tendency to easily form perfect crystals. However, since the reaction is in a liquid phase state and at a relatively low temperature, a small amount of incomplete crystals may exist at the same time. Therefore, the inventors believe that the above method may easily form a form in which the [A300] / [A210] described later meets a specific range (0.045 to 0.070).
[0082] On the other hand, in the method using seed crystals, the conditions with relatively high HMR (large amount of water) are preferred compared to the method without seed crystals. It is believed that since it can be predicted that this tends to promote crystallization by seed crystals, the conditions with relatively high HMR, which are considered to have a higher degree of freedom of the silica component in the sol, are preferred in the method using seed crystals.
[0083] When the MSE-type aluminosilicate is used as the so-called seed crystal in the first step of the present invention, even in the state containing the sol-like silica, as long as the HMR value is set to the specific range, the effect of promoting the crystal growth during the synthesis of the aluminosilicate will be shown, so it is preferred. In addition, in the first step of the manufacturing method of the present invention, since sol-like silica is used, at least in the initial stage, the silica and the above-mentioned metal compound (AL), preferably zeolite, are in contact with each other in a state where there is a lot of water derived from the sol-like silica. It can also be considered that the water has the effect of promoting the reaction with the above-mentioned metal compound (AL), preferably zeolite and other components. In addition, by controlling to meet the above-mentioned HMR range, the effect of promoting the above-mentioned crystal growth may also be shown.
[0084] When the seed crystals are used, the amount thereof is preferably 1 to 40% by weight, more preferably 2 to 30% by weight, of the silicon dioxide as the silicon source. In addition, the metal compound (AL), preferably zeolite, as the aluminum source also acts as a silicon source, and the amount thereof is preferably 5 to 50% by weight, more preferably 8 to 40% by weight, of the silicon dioxide.
[0085] The aluminosilicate thus obtained preferably has a highest peak (β) in the region of 17.5 to 35° and in the region of 20° or more and less than 22.5° in XRD measurement, and the peak intensity ratio of the peak (β) to the highest peak (γ) in the region of 25 to 27° is preferably in the range of 1.60 to 5.0. The more preferred lower limit of the peak intensity ratio is 1.65, further preferably 1.68, and particularly preferably 1.70. On the other hand, the preferred upper limit is 4.5, and more preferably 4.4.
[0086] The reason is not clear at this stage, but when such aluminosilicate is used, a suitable catalyst for aromatic polyhydroxy compounds can be obtained by using a method such as introducing a titanium source as described later. Therefore, aluminosilicate having a structure of a diffraction pattern in XRD measurement as described above is part of a preferred embodiment of the present invention.
[0087] The aluminosilicate of the present invention shows a crystal structure, but it is estimated that its crystal form may be different from that of conventional aluminosilicates and may include a slightly unstable structure or an unstable structure (particularly based on the value of the peak intensity ratio of the peak (β) to the peak (γ)). It is also estimated that in the case of a modified aluminosilicate described later, such instability leads to excellent performance as a catalyst for producing an aromatic polyhydroxy compound.
[0088] It should be noted that when the elements selected from the group consisting of Group 4 and Group 5 of the periodic table described later in the present invention are introduced into the sintered product of aluminosilicate obtained through the second and third steps described later, it can be considered that the introduction site of the above-mentioned elements is mainly the solid surface of the sintered product of aluminosilicate, and therefore it can be considered that the crystal structure is roughly the same before and after the introduction of the above-mentioned elements.
[0089] Examples of the raw material of the sol-like silica include colloidal silica, sodium silicate, wet silica, dry silica, etc. These silicon sources may be used alone or in combination of two or more.
[0090] The above-mentioned metal compound (AL) as the aluminum source may also be used in combination of two or more. Preferably, it includes zeolite. As a component other than the above-mentioned zeolite, for example, a water-soluble aluminum compound can be used. As a water-soluble aluminum compound, for example, aluminum hydroxide, sodium aluminate, aluminum nitrate, aluminum sulfate, etc. can be cited.
[0091] As the above-mentioned alkali source, for example, a hydroxide containing an alkali metal can be used. As the hydroxide containing an alkali metal, for example, sodium hydroxide, potassium hydroxide, etc. can be mentioned. These alkali sources can be used alone or in combination of two or more.
[0092] As the organic structure directing agent, N,N,N',N'-tetraethylbicyclo[2,2,2]oct-7-ene-2,3:5,6-dipyrrolidine is preferably used. Diiodide, N,N,N',N'-tetraethylbicyclo[2,2,2]oct-7-ene-2,3:5,6-dipyrrolidine A known compound such as diiodide.
[0093] The aluminosilicate is preferably calcined before the second step described later. There are no particular restrictions on the calcination method, and examples thereof include a method of calcining using an electric furnace, a gas furnace, etc. As calcination conditions, it is preferred to heat in an air atmosphere for 0.1 to 20 hours. The calcination temperature is preferably 500 to 800°C, and more preferably 550 to 750°C.
[0094] 〔Second process〕
[0095] The second step is a step of treating the aluminosilicate obtained in the first step with an acid, in other words, a step of bringing the aluminosilicate into contact with the acid.
[0096] As the acid used in this process, for example, inorganic acids, organic acids and mixtures thereof can be cited, and as specific examples thereof, for example, nitric acid, hydrochloric acid, sulfuric acid, citric acid, oxalic acid and mixtures thereof can be cited. Among them, it is preferred to include an acid containing an element selected from the 15th and 16th group elements of the periodic table, and nitric acid is particularly preferred. The concentration of the acid is not particularly limited, and is preferably 5% to 80% by weight, and more preferably 40% to 80% by weight. When the acid is used in the form of an aqueous solution, its usage is preferably 1 to 100 parts by weight relative to 1 part by weight of aluminosilicate. A more preferred lower limit is 2 parts by weight, more preferably 3 parts by weight, and particularly preferably 5 parts by weight. On the other hand, a more preferred upper limit is 80 parts by weight, more preferably 70 parts by weight, particularly preferably 60 parts by weight, and particularly preferably 50 parts by weight.
[0097] The temperature condition for contacting the aluminosilicate with the acid is preferably 50°C to 170°C, more preferably 130°C to 170°C. In addition, the time for the acid treatment is preferably 5 hours to 48 hours, more preferably 12 hours to 36 hours. A further preferred lower limit of the time is 18 hours. It can be considered that a portion of the aluminum is removed from the aluminosilicate by contact with the acid. It is speculated that the aluminum on the surface of the aluminosilicate is mainly removed. It can be speculated that by selecting the conditions of relatively high temperature and long time as described above, a structure that is conducive to the introduction of the above-mentioned Group 4 elements and Group 5 elements can be easily formed in the calcination treatment in the third step described later.
[0098] 〔Third process〕
[0099] In the third step, the treated product obtained in the second step, that is, the aluminosilicate after contact with the acid, is calcined once. There is no particular limitation on the calcining method, and for example, a calcining method using an electric furnace, a gas furnace, etc. can be cited. As calcining conditions, it is preferred to heat in an air atmosphere for 0.1 hours to 20 hours. The calcining temperature is 550°C to 850°C, and more preferably 600°C to 800°C. It can be inferred that by calcining once in this relatively high temperature environment, an environment that is conducive to the formation of the so-called modified aluminosilicate obtained in the fourth step, which contains elements of Group 4 and Group 5 of the periodic table represented by titanium species, can be obtained in a highly active state.
[0100] Before the aluminosilicate in contact with the acid is calcined, it is preferred to filter the treated product using a suction filter (Nutsche) or the like, separate the acid (aqueous solution) or the like used, and then wash the solid portion (filter cake) with water and dry it. The above-mentioned washing step is preferably carried out in a wet state without drying before washing. There is no particular limitation on the drying method after washing, but it is preferably dried uniformly and quickly, for example, external heating methods such as hot air drying and superheated water vapor drying, microwave heating drying, and electromagnetic wave heating methods such as high-frequency dielectric heating drying can be used.
[0101] [Fourth process]
[0102] In the fourth step, the calcined product obtained in the third step (hereinafter also referred to as "primary calcined product") is contacted with a liquid containing one or more elements selected from the 4th group and the 5th group of the periodic table as an element source in a liquid phase state, and then dried and calcined for the second time. Examples of the 4th group and the 5th group of the periodic table include titanium, zirconium, hafnium, vanadium, etc. Preferred elements are titanium, zirconium, and vanadium, and titanium is particularly preferred. As compounds containing these elements, halides, alkoxides, or salts of inorganic acids of each element can be cited as suitable compounds. More preferably, the halide contains chlorides, and the alkoxide contains alkoxy groups having 1 to 6 carbon atoms. As further preferred alkoxides, ethanolates, butoxides (n-butoxides, isobutoxides, sec-butoxides, tert-butoxides), sulfates, etc. can be cited. Two or more of these compounds can be used in combination.
[0103] Hereinafter, an embodiment in which titanium is used as a liquid (liquid phase titanium source), which is the most preferred embodiment among the Group 4 and Group 5 elements of the periodic table, will be described as a representative example.
[0104] The liquid titanium source is a liquid containing titanium. Examples of the liquid containing titanium include a liquid titanium compound itself or an aqueous solution of a titanium compound. Among them, a titanium compound that is substantially acidic in a liquid state is preferred.
[0105] As liquid titanium compounds, for example, titanium tetrachloride (TiCl4), tetrabutyl titanate, etc. can be cited, among which titanium tetrachloride is preferred. As aqueous solutions of titanium compounds, for example, titanium tetrachloride aqueous solution, titanium trichloride (TiCl3) aqueous solution, titanium sulfate (Ti(SO4)2) aqueous solution, potassium hexafluorotitanate aqueous solution, etc. can be cited, among which titanium tetrachloride aqueous solution, titanium trichloride aqueous solution, titanium sulfate aqueous solution are preferred. In the present invention, in addition to titanium tetrachloride, even when titanium sources with lower reactivity than titanium tetrachloride, such as titanium trichloride and titanium sulfate, are used, the catalytic activity described below can be exhibited.
[0106] The above-mentioned titanium-containing liquid can be used alone or in combination of two or more. The titanium-containing liquid can use a commercial product, or a liquid appropriately prepared by diluting a solid titanium compound with water to a desired concentration. Compared with a gas phase titanium source, a liquid phase titanium source (titanium-containing liquid) is not easy to leak, and the corrosion problem of manufacturing equipment, analytical instruments, etc. is also improved, so it can be expected to be easy to manufacture industrially.
[0107] The conditions for bringing the primary burnt product into contact with the titanium source are not particularly limited, but titanium is introduced into the primary burnt product of the aluminosilicate by the contact. The introduction of the titanium can be considered to be the introduction of titanium at the position of the aluminum that is believed to be removed in the second step, or a reaction in which a part of the aluminum of the aluminosilicate is replaced by titanium. As specific conditions of this step, for example, when a liquid titanium compound itself is used, it is preferred to add 5 to 300 parts by weight of the liquid titanium compound per 1 part by weight of the primary burnt product, and more preferably 20 to 250 parts by weight. When an aqueous solution of the titanium compound is used, it is preferred to add 1 to 10 parts by weight of the aqueous solution of the titanium compound per 1 part by weight of the primary burnt product, and more preferably 1 to 7 parts by weight. The concentration of the aqueous solution varies depending on the compound used, and is, for example, 10 to 70% by weight, and preferably 15 to 60% by weight.
[0108] The amount of the titanium compound in the aqueous solution is preferably 0.1 g, more preferably 0.2 g, further preferably 0.3 g, and particularly preferably 0.5 g per 1 g of the primary calcined product, and preferably 10 g, more preferably 5 g, and further preferably 3 g.
[0109] The contact between the titanium source and the aluminosilicate after the primary firing may be carried out only once, or the components may be used in multiple batches, as long as the weight ratio used is within the range of the added amount. For example, the titanium source may be added to the primary fired product, and the fired product obtained by drying and secondary firing described below may be further added with the titanium source to be dried and fired again. When adding the titanium source, hydrogen chloride is generated by the reaction of moisture in the air with the titanium compound, so it is preferably carried out under a nitrogen atmosphere.
[0110] As a more specific preferred method, there can be mentioned a method in which the primary calcined product is brought into contact with a titanium source, fully mixed, the mixture is subjected to a heat treatment, and the mixture is fully dried by the same method as the drying method exemplified in the third step, and then a secondary calcination is performed. The temperature in the above-mentioned heating treatment and drying treatment is not particularly limited. For example, in order to effectively introduce titanium into the primary calcined product, it is preferably in the range of 20 to 150°C. A more preferred lower limit is 30°C, more preferably 40°C, and particularly preferably 50°C. On the other hand, a more preferred upper limit is 140°C, more preferably 120°C, and particularly preferably 100°C. The time required for the above-mentioned process is also not particularly limited, and is preferably 0.1 to 24 hours. A more preferred lower limit is 0.3 hours, more preferably 0.4 hours, and particularly preferably 0.5 hours. On the other hand, a more preferred upper limit is 12 hours, and more preferably 6 hours. There is no particular limitation on the method for secondary calcination, and for example, calcination can be performed using an electric furnace, a gas furnace, or the like. As the calcination conditions, it is preferred to carry out the calcination at 400°C to 850°C for 0.1 to 20 hours in an air atmosphere. The lower limit of the calcination temperature is more preferably 500°C, more preferably 550°C, and particularly preferably 600°C. On the other hand, the upper limit is more preferably 800°C, more preferably 750°C, and particularly preferably 700°C.
[0111] The temperatures for the primary firing and the secondary firing can be selected independently. In some cases, it is preferred that the temperature for the secondary firing be higher than the temperature for the primary firing.
[0112] Through the fourth step, for example, a crystalline porous alumino-titano-silicate in which a part of aluminum in the crystalline porous aluminosilicate is substituted with titanium can be obtained, which is considered to be a preferred embodiment of the modified aluminosilicate of the present invention.
[0113] Before the drying treatment, the mixture of the titanium source and the primary calcined product may be heated to remove moisture in advance, the mixture may be filtered to remove impurities, and washed with an organic solvent before drying and secondary calcination.
[0114] The above-mentioned production conditions can also be applied when an element other than titanium is used.
[0115] As an example of a compound of a Group 4 element of the periodic table that can replace the above-mentioned titanium source, zirconium tetrachloride, tetraalkoxy zirconium, hafnium tetrachloride, tetraalkoxy hafnium, zirconium sulfate, etc. can be used in combination with water, alcohol, ether, etc. as needed, and liquefied for use. For example, aqueous solutions of these compounds, solutions of alcohol, ether, etc., etc. can be cited. In addition, as an example of a compound of a Group 5 element of the periodic table that can replace the above-mentioned titanium source, vanadium pentachloride, vanadium sulfate, vanadium trichloride and alkoxy substitutions thereof, etc. can be used in combination with water, alcohol, ether, etc. as needed, and liquefied for use. For example, their aqueous solutions and solutions of alcohol, ether, etc. can be cited.
[0116] 〔Modified Aluminosilicate〕
[0117] The modified aluminosilicate obtained in the fourth step is preferably a crystalline porous aluminosilicate having crystallinity and porosity, similar to the raw material aluminosilicate obtained in the first step, more preferably a crystalline porous aluminosilicate having an MSE skeleton, further preferably a crystalline porous aluminosilicate having a UZM-35, MCM-68, or YNU-3 structure, and particularly preferably a crystalline porous aluminum titanosilicate. The so-called crystallinity can be considered to be the same as that described for the aluminosilicate as the raw material.
[0118] The crystalline porous aluminosilicate refers to a porous crystal having at least a portion of SiO4 tetrahedrons with oxygen arranged at four vertices with silicon as the center and AlO4 tetrahedrons with aluminum arranged instead of silicon in the center, which are regularly three-dimensionally bonded, and can be said to be a type of zeolite containing aluminosilicate. The modified aluminosilicate having crystallinity and porosity is obtained, for example, by the following method: the crystalline porous aluminosilicate skeleton contains aluminum and one or more elements selected from the group consisting of the fourth group elements and the fifth group elements of the periodic table, preferably a method in which a portion of the aluminum in the crystalline porous aluminosilicate skeleton is replaced by one or more elements selected from the group consisting of the fourth group elements and the fifth group elements of the periodic table. As a more preferred example, when one or more elements selected from the group consisting of elements of Group 4 and Group 5 of the periodic table is titanium, the crystalline porous modified aluminosilicate becomes a crystalline porous aluminum titanosilicate, and the crystalline porous aluminum titanosilicate is obtained by including aluminum and titanium in the aluminosilicate skeleton, preferably replacing a part of the aluminum in the skeleton with titanium.
[0119] The crystalline porous aluminosilicate having an MSE skeleton has a three-dimensional pore structure, and the three-dimensional pore structure has a 10-membered ring structure formed by 10 tetrahedral units and a 12-membered ring structure formed by 12 tetrahedral units in an arbitrary ratio. It is believed that due to the pores having the above-mentioned 12-membered ring structure, the matrix easily diffuses into the pores, and high catalytic activity is easily obtained. In addition, since there is no large cavity inside the pores, it is believed that one of the factors that easily show para-selectivity in the oxidation reaction of phenol.
[0120] It is well known that porous compounds have a large specific surface area. The specific surface area of the modified aluminosilicate of the present invention is preferably 50 to 1000 m 2 / g. The lower limit of the specific surface area is more preferably 100 m 2 / g, more preferably 150m 2 On the other hand, the upper limit of the specific surface area is more preferably 800 m 2 / g, more preferably 600m 2 / g.
[0121] The value of the specific surface area can be determined by preparing a BET curve from the measurement results using a known nitrogen adsorption-desorption measuring apparatus (eg, BELSORP-max manufactured by Microtrac BEL Co., Ltd.), and by a known calculation method based on the BET theory.
[0122] The preferred pore volume range of the modified aluminosilicate of the present invention is 0.1 to 0.5 cm 3 / g, more preferably 0.15 to 0.4 cm 3 / g.
[0123] The content of the Group 4 element and the Group 5 element contained in the modified aluminosilicate of the present invention is not particularly limited. For example, when titanium is included as one or more elements selected from the group consisting of Group 4 elements and Group 5 elements contained in the modified aluminosilicate, the molar ratio of silicon to titanium ([Si] / [Ti]) is preferably in the range of 0.1 to 400, more preferably in the range of 50 to 300, further preferably in the range of 100 to 280, and most preferably in the range of 150 to 260.
[0124] When a compound that is easy to crystallize itself, such as TiCl3, is used, the element may be introduced into the surface of the aluminosilicate in the form of a cluster or a crystal. In this case, since the apparent element content sometimes increases, the [Si] / [Ti] ratio tends to become a small value. The [Si] / [Ti] ratio in this case is preferably in the range of 0.5 to 30. A more preferred lower limit is 1, and a more preferred upper limit is 1.2. On the other hand, a more preferred upper limit is 20, and a more preferred upper limit is 15.
[0125] There is no particular limitation on the aluminum content of the modified aluminosilicate of the present invention. The molar ratio of silicon to aluminum ([Si] / [Al]) is preferably in the range of 5 to 100,000, more preferably in the range of 10 to 10,000, and further preferably in the range of 15 to 1,000.
[0126] The modified aluminosilicate of the present invention preferably has characteristics in absorption in a specific wavelength region in ultraviolet-visible absorption spectrum measurement.
[0127] The modified aluminosilicate of the present invention contains an element selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table, and the absorbance at 300 nm (A
[300] ) of the ultraviolet-visible absorption spectrum is usually preferably 1.0 or more. Specific examples and preferred examples of the element selected from Group 4 and Group 5 elements contained in the modified aluminosilicate of the present invention are the same as those in the above-mentioned "Fourth Step" item.
[0128] In addition, when the element selected from the group consisting of the elements of Group 4 and Group 5 of the periodic table is contained in a tetravalent or pentavalent state in the modified aluminosilicate satisfying the preferred XRD requirements, or when a tetravalent or pentavalent compound of the element selected from the group consisting of the elements of Group 4 and Group 5 of the periodic table is used in the fourth step, the A
[300] is preferably a value exceeding 0.20 (hereinafter also referred to as "specific requirement 0"). In addition, for example, when the specific requirement described later (A
[300] / A
[210] is 0.045 or more and 0.070 or less: hereinafter also referred to as "specific requirement 1") is satisfied, the A
[300] is sometimes preferably in the range of 0.07 to 0.20, more preferably in the range of 0.07 to 0.15, and particularly preferably in the range of 0.07 to 0.10.
[0129] When the A
[300] is less than 1.0, or less than 0.20 in the case of the specific requirement 0, and further less than 0.07 in the case of satisfying the specific requirement 1, when the aromatic dihydroxy compound is produced by the reaction of phenols and hydrogen peroxide, the selectivity of the aromatic dihydroxy compound tends to be relatively low. It should be noted that the method for measuring the absorbance is not particularly limited, and it can be the result of measuring by any method of the transmission method and the reflection method. In the case of measuring by the reflection method, the reflected light sometimes includes diffuse reflected light in addition to the regular reflected light, but for convenience, it is assumed that all are regular reflected light and calculated.
[0130] Although the detailed mechanism is not clear, the present inventors presume as follows (hereinafter, the modified aluminosilicate is described by taking a crystalline porous aluminotitanium silicate in which the element selected from Group 4 and Group 5 is titanium as an example).
[0131] It can be inferred that aluminum and titanium exist in the skeleton surface of crystalline porous aluminum titanium silicate. In addition, it can be considered that they preferably exist centered on the inside of the concave parts such as the pores of the crystalline porous aluminum titanium silicate. Here, for example, in the case of a method of manufacturing using high-temperature gaseous titanium tetrachloride recorded in patent documentation 3, which is considered to include only titanium that is completely incorporated without defects in the skeleton of the crystal structure, it is inferred that the absorbance near 300nm of the ultraviolet visible absorption spectrum is difficult to reach more than 1.0 or difficult to reach more than 0.2 in the above-mentioned specific requirement 0. In such a range, it can be considered to be in a state where there is slightly unstable titanium. In other words, it can be inferred that the crystalline porous aluminum titanium silicate that meets the requirements of the present invention has a lot of titanium that is not completely incorporated into its basic skeleton structure and becomes an unstable structure. Such titanium species contribute greatly to the reaction of forming aromatic dihydroxy compounds. When the oxidation reaction of phenols by hydrogen peroxide proceeds, the instability thereof leads to the generation of 1,2-hydroxy compounds (e.g., catechol) which are considered to be sterically unfavorable, and the generation of benzoquinone which is a form after the reaction proceeds further is suppressed, and it is presumed that 1,4-type aromatic dihydroxy compounds can be produced with high selectivity.
[0132] From the perspective of further improving the selectivity of the aromatic dihydroxy compound, the preferred lower limit of A
[300] of the modified aluminosilicate is 1.5, and more preferably 1.8. In addition, in the case of the above-mentioned specific requirement 0, the more preferred lower limit of the above-mentioned A
[300] is 0.08, more preferably 0.25, and particularly preferably 0.30. On the other hand, the setting of the upper limit of A
[300] has no substantial significance, but the preferred upper limit is 15, and more preferably 10. In addition, for a conventional highly crystalline porous aluminum titanosilicate, A
[300] is 0.2 or less.
[0133] In addition, the ratio (A
[300] / A
[210] ) of A
[300] in the ultraviolet-visible absorption spectrum of the modified aluminosilicate to the absorbance at 210 nm (A
[210] ) is more preferably 0.5 or more, further preferably 0.6 or more, and particularly preferably 0.8 or more. In addition, in the case of the above-mentioned specific requirement 0, the above-mentioned A
[300] / A
[210] is preferably a value exceeding 0.10. The more preferred lower limit is 0.11. On the other hand, for example, in the case of a small value of less than 0.20, the above-mentioned A
[300] / A
[210] is sometimes preferably in the range of 0.045 to 0.070. For example, it is believed that in the case of titanium incorporated without defects in the framework of the crystal structure, since A
[210] is relatively high relative to A
[300] , A
[300] / A
[210] in a common crystalline porous aluminum titanosilicate tends to be 0.1 or less, but when it is 0.045 or more, titanium with a special unstable structure is slightly contained, and this titanium may show an activation effect alone or show an activation effect that affects other titanium, etc. It is believed that the unstable titanium that may be slightly present in this way has high reactivity and structural selectivity, and may show suitable performance such as high activity, high yield, and high position selectivity in the production of hydroquinone, etc. described later.
[0134] The upper limit of A
[300] / A
[210] is not particularly significant, but is more preferably 1.5, and even more preferably 1.0. In addition, when it is considered that unstable titanium is slightly present as described above, the upper limit is preferably 0.070.
[0135] It should be noted that the above-mentioned ultraviolet-visible absorption spectrum can be measured by a conventional method, for example, the following method can be mentioned.
[0136] "A method in which 0.1 g of a solid aluminosilicate sample is placed in a sample cell with an optical path length of 10 mm and the wavelength is measured in the range of 200 to 800 nm using a UV-2550 ultraviolet-visible spectrophotometer manufactured by Shimadzu Corporation."
[0137] It should be noted that the above-mentioned solid aluminosilicate sample is preferably used after being fully dried.
[0138] The modified aluminosilicate obtained by the production method of the present invention can be used as a catalyst for producing an aromatic polyhydroxy compound according to one embodiment of the present invention.
[0139] <Method for producing aromatic polyhydroxy compounds>
[0140] One embodiment of the present invention is a method for producing an aromatic polyhydroxy compound, comprising: reacting an aromatic hydroxy compound with hydrogen peroxide in the presence of a catalyst for producing an aromatic polyhydroxy compound containing the modified aluminosilicate.
[0141] Examples of the aromatic hydroxy compound include phenols described below and compounds having a structure in which one hydroxyl group is bonded to a phenyl skeleton, such as hydroxynaphthalene and its derivatives, hydroxyanthracene and its derivatives, and hydroxyfluorene and its derivatives. Phenols are preferred.
[0142] Examples of hydrogen peroxide include hydrogen peroxide and compounds in which one hydrogen in hydrogen peroxide is replaced by an aliphatic or aromatic hydrocarbon group, a hydrocarbon group containing a heteroatom, etc., such as butyl hydroperoxide, cumyl hydroperoxide, etc. Hydrogen peroxide is preferred, and more specifically, hydrogen peroxide is a preferred embodiment.
[0143] The following is a description of the method for producing an aromatic polyhydroxy compound, taking a method for producing an aromatic dihydroxy compound as an example. When, for example, phenols are reacted with hydrogen peroxide in the presence of the modified aluminosilicate of the present invention, an aromatic dihydroxy compound can be produced with high selectivity.
[0144] The phenols include unsubstituted phenols and substituted phenols. Examples of substituted phenols include alkylphenols substituted with a linear or branched alkyl or cycloalkyl group having 1 to 6 carbon atoms such as methyl, ethyl, isopropyl, butyl, hexyl, etc.
[0145] Examples of phenols include phenol, 2-methylphenol, 3-methylphenol, 2,6-dimethylphenol, 2,3,5-trimethylphenol, 2-ethylphenol, 3-isopropylphenol, 2-butylphenol, and 2-cyclohexylphenol, among which phenol is preferred. In addition, when both the 2-position and the 6-position of the phenol have substituents, the product is only a hydroquinone derivative.
[0146] As the aromatic dihydroxy compound of the reaction product, for example, hydroquinones (substituted or unsubstituted hydroquinone), catechols (substituted or unsubstituted catechol) and the like can be mentioned, and their specific examples include hydroquinone, catechol, 2-methylhydroquinone, 3-methylcatechol, 4-methylcatechol, 3-methylhydroquinone, 1,4-dimethylhydroquinone, 1,4-dimethylcatechol, 3,5-dimethylcatechol, 2,3-dimethylhydroquinone, 2,3-dimethylcatechol and the like.
[0147] The modified aluminosilicate obtained in the present invention is used as a catalyst for the manufacture of aromatic dihydroxy compounds. As a filling method of the catalyst, various methods such as a fixed bed, a fluidized bed, a suspended bed, a tray-type fixed bed, etc. are adopted, and it can be implemented in any way. In addition, the above-mentioned catalyst can be used directly or molded according to the filling method of the catalyst. As a molding method of the catalyst, there are generally extrusion molding, tablet molding, tumble granulation, spray granulation, etc. When the catalyst is used in a fixed bed manner, extrusion molding or tablet molding is preferred. In the case of a suspended bed method, spray granulation is preferred. It can also be dried and calcined after spray granulation. The average particle size of the catalyst after spray granulation is preferably 0.1μm to 1000μm, and more preferably in the range of 5μm to 100μm. If it is above 0.1μm, it is easy to filter the catalyst, so it is preferred; if it is below 1000μm, the catalyst has good performance and strong strength, so it is preferred.
[0148] The amount of the catalyst used is preferably 0.1 to 30% by mass, more preferably 0.4 to 20% by mass, relative to the total mass of the reaction solution (the total mass of the liquid components in the reaction system, excluding the mass of fixed components such as the catalyst) in terms of outer percentage. If it is 0.1% by mass or more, the reaction is completed in a short time, and the productivity is improved, so it is preferred. If it is 30% by mass or less, it is preferred in that the amount of catalyst separated and recovered is small.
[0149] When the modified aluminosilicate of the present invention is used as a catalyst in a method for producing an aromatic dihydroxy compound, it may be combined with other components. For example, the siloxane compound described in the above-mentioned patent document 1 and the specific alcohol compound described in the above-mentioned patent document 2 may be cited. Such components are preferably used in a ratio of 5 to 90% by mass of the mass of the above-mentioned reaction solution. More preferably, it is 8 to 90% by mass.
[0150] In addition, the molar ratio of hydrogen peroxide to phenol is preferably 0.01 or more and 1 or less. In addition, the concentration of hydrogen peroxide used is not particularly limited, and a conventional 30% aqueous solution can be used, and a high-concentration hydrogen peroxide solution can also be used directly, or it can be used after diluting with an inactive solvent in the reaction system. As the solvent used for dilution, alcohols, water, etc. can be mentioned. Hydrogen peroxide can be added all at once, or it can be added gradually over time.
[0151] The reaction temperature is preferably in the range of 30° C. to 130° C., more preferably in the range of 40° C. to 100° C. The reaction proceeds at temperatures outside this range, but the above range is preferred from the viewpoint of improving productivity. The reaction pressure is not particularly limited.
[0152] The reaction method is not particularly limited, and the reaction can be carried out in any of batch, semi-batch, and continuous methods. In the case of continuous reaction, the reaction can be carried out in a uniform mixing tank of a suspended bed, or in a plug flow form of a fixed bed flow method, or multiple reactors can be connected in series and / or in parallel. From the viewpoint of equipment cost, the number of reactors is preferably 1 to 4. In addition, when multiple reactors are used, hydrogen peroxide can also be added to multiple reactors in batches.
[0153] In order to obtain an aromatic dihydroxy compound from the reaction solution, the reaction solution or the separated solution containing the dihydroxy compound after separation of the catalyst may be subjected to a purification treatment to remove unreacted components and by-products. The purification treatment is preferably performed on the separated solution containing the aromatic dihydroxy compound after separation of the catalyst.
[0154] There is no particular limitation on the method of purification treatment, and specific examples include oil-water separation, extraction, distillation, crystallization, and combinations thereof. The method and procedure of purification treatment are not particularly limited, and for example, the reaction solution and the separated solution containing the aromatic dihydroxy compound after separation of the catalyst can be purified by the following method.
[0155] When the reaction liquid is separated into two phases, an oil phase and an aqueous phase, oil-water separation can be performed. By oil-water separation, the aqueous phase with a low content of dihydroxy compounds is removed and the oil phase is recovered. In this case, the aromatic dihydroxy compounds can be recovered by extraction, distillation, etc. for the separated aqueous phase, or a part or all of it can be used again for the reaction. In addition, the catalyst separated in the above-mentioned catalyst separation step or the catalyst after drying treatment can be dispersed in the separated aqueous phase and supplied to the reactor. On the other hand, for the oil phase, it is preferred to further perform a refining treatment by extraction, distillation and crystallization.
[0156] For example, a solvent such as 1-butanol, toluene, isopropyl ether, methyl isobutyl ketone, etc. is used in the extraction. If the extraction and oil-water separation are combined, the oil-water separation can be carried out efficiently. The extraction solvent is preferably separated and recovered by a distillation column and recycled.
[0157] The distillation may be performed on the reaction liquid immediately after the catalyst is separated, or on the oil phase and the water phase after the oil-water separation. Furthermore, the extract may be distilled. When the reaction liquid immediately after the catalyst is separated is distilled, it is preferred to first separate light boiling components such as water or alcohols. Water and alcohols may be separated in different distillation towers or in one distillation tower.
[0158] It is also possible to separate water and alcohols by the above-mentioned oil-water separation, extraction, distillation operation, etc., and then recover phenols in the next distillation operation and use them again for the reaction. In the case where the recovered phenols contain unseparated water, isopropyl ether or toluene can be added to remove it by azeotropic distillation.
[0159] This azeotropic distillation can also be performed on the water before phenol recovery and the liquid after alcohol separation. The separated water can be used for reaction again or as waste water. In the case where the recovered phenols contain impurities such as reaction byproducts in addition to water, they can also be further separated by distillation. In the case where the impurities are reaction byproduct quinones, they can be supplied to the reactor again together with the phenols.
[0160] After the separation of phenols, components with a higher boiling point than the aromatic dihydroxy compounds are removed by distillation, and hydroquinones and catechols can be separated by the next distillation operation. In addition, the high boiling point components, hydroquinones and catechols can also be separated by a single distillation operation by extracting hydroquinones from the middle stage of the distillation column.
[0161] The obtained hydroquinones and catechols can be subjected to distillation, crystallization, or the like to remove impurities and improve purity as necessary.
[0162] In the presence of the modified aluminosilicate of the present invention, for example, when phenol and hydrogen peroxide are reacted, there is a tendency to generate hydroquinone with a high yield. In addition, compared with catechol and benzoquinone, there is a tendency to generate hydroquinone with a high selectivity. Therefore, it can be said that the industrial value of the modified aluminosilicate of the present invention is high. Aromatic polyhydroxy compounds can also be manufactured under the same conditions as the manufacture method of the above-mentioned aromatic dihydroxy compounds.
[0163] Example
[0164] Hereinafter, the present invention will be described in more detail by way of examples, but the present invention is not limited to these examples.
[0165] 〔XRD measurement method〕
[0166] The X-ray diffraction phenomenon of the crystal as a sample was measured by a conventional method except for the following conditions.
[0167] · X-ray diffraction apparatus: Model: MultiFlex manufactured by RIGAKU Co., Ltd.
[0168] X-ray source: CuKα
[0169] Output power: 40kV / 40mA
[0170] Divergence slit: 1°
[0171] Scattering slit: 1°
[0172] Light receiving slit: 0.30mm
[0173] 2θ: 3~50°
[0174] [Measurement method of UV-visible absorption spectrum]
[0175] 0.1 g of solid aluminosilicate sample was placed in a sample cell with an optical path length of 10 mm. Using a UV-2550 ultraviolet-visible spectrophotometer manufactured by Shimadzu Corporation, the absorption intensity at wavelengths of 300 nm and 210 nm was measured in the range of 200 to 800 nm by conventional methods.
[0176] [Example 1]
[0177] [Preparation of Crystal (A1)]
[0178] The crystal (A1) having an MSE framework was prepared by the following method.
[0179] First, 7.90 g of (8 mol / L) NaOH aqueous solution, 8.18 g of (8 mol / L) KOH aqueous solution, 20.46 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 33.82 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content 40 mass%)) were placed in a container and stirred at 80°C to obtain a sol-like substance. The stirring time was then adjusted so that the HMR value became 3.20. At this time, the raw material was solidified.
[0180] Then, 6.91 g of FAU zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) was added to the obtained block material and mixed using a mortar. Then, the mixture was placed in an autoclave and heated at 160° C. for 68 hours. The cooled mixture was filtered and washed with water, and vacuum dried at 70° C. for 2 hours to obtain crystals (A1). The highest diffraction peak determined by XRD was observed at 21.66°.
[0181] [First step: preparation of aluminosilicate]
[0182] Next, 7.81 g of (8 mol / L) NaOH aqueous solution, 8.09 g of (8 mol / L) KOH aqueous solution, 24.36 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 36.13 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content is 40 mass%)) are placed in a container, stirred at 80°C to obtain a sol-like substance, and 0.79 g of the above-mentioned crystals (A1) and 6.78 g of FAU-type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) are added and mixed. The stirring time is adjusted so that the HMR value at this stage becomes 4.00. The contents are heated at 165°C for 40 hours using the same autoclave as above. Then, the cooled mixture is filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (1-0).
[0183] The highest peak in the 17.5-35° region of the crystal (1-0) measured by XRD was observed at 21.6°, and the intensity ratio of the peak observed at 25.78° as the highest peak in the 25.0-27.0° region was 1.73. Figure 1 The above crystal (1-0) was calcined at 550°C for 10 hours to obtain a crystal (1-1).
[0184] [Second step: contact with acid, third step: primary calcination]
[0185] 2 g of the above-prepared crystal (1-1) and 80 g of 65% nitric acid were added to a container and mixed, and the mixture was placed in an autoclave and heated at 148° C. for 24 hours. The cooled mixture was filtered and washed with water, air-dried for 1 day, and then calcined at 600° C. for 2 hours to obtain crystal (1-2).
[0186] [Fourth step: contact with titanium compound, secondary calcination]
[0187] 1 g of the crystal (1-2) prepared above and 5 g of a titanium tetrachloride aqueous solution having a Ti concentration of 16% were placed in a container, and heated and stirred at 40°C for 1 hour using an oil bath. Water was then added, filtered, and further washed, and the dried product was secondary calcined at 650°C for 2 hours to obtain a crystalline porous aluminum titanosilicate (crystal (1-3)).
[0188] [Example 2]
[0189] [Preparation of Crystal (A2)]
[0190] The crystal (A2) having an MSE framework was prepared by the following method.
[0191] First, 15.60 g of (8 mol / L) NaOH aqueous solution, 16.22 g of (8 mol / L) KOH aqueous solution, 40.60 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 67.20 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content 40 mass%)) were placed in a container and stirred at 80°C to obtain a sol-like substance. The stirring time was then adjusted so that the HMR value became 3.50. At this time, the raw material was solidified.
[0192] Then, 13.56 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) was added to the obtained block material and mixed using a mortar. Then, the mixture was placed in an autoclave and heated at 165° C. for 40 hours. The cooled mixture was filtered and washed with water, and vacuum dried at 70° C. for 2 hours to obtain crystals (A2). The highest diffraction peak determined by XRD was observed at 21.60°.
[0193] [First step: preparation of aluminosilicate]
[0194] Next, 7.78 g of (8 mol / L) NaOH aqueous solution, 8.17 g of (8 mol / L) KOH aqueous solution, 24.34 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 35.33 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content is 40 mass%)) are placed in a container, stirred at 80°C to obtain a sol-like substance, and 0.79 g of the above-mentioned crystals (A2) and 6.78 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) are added and mixed. The stirring time is adjusted so that the HMR value at this stage becomes 4.80. Then, the mixture is placed in an autoclave and heated at 160°C for 37 hours. Then, the cooled mixture is filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (2-0).
[0195] The highest peak in the 17.5-35° region of the crystal (2-0) measured by XRD was observed at 21.6°, and the intensity ratio of the peak observed at 26.08° as the highest peak in the 25.0-27.0° region was 4.30. The XRD spectrum is as follows Figure 1 shown.
[0196] The above crystal (2-0) was calcined at 550°C for 10 hours to obtain a crystal (2-1).
[0197] [Second step: contact with acid, third step: primary calcination]
[0198] Crystal (2-2) was obtained in the same manner as in Example 1 except that Crystal (2-1) was used instead of Crystal (1-1).
[0199] [Fourth step: contact with titanium compound, secondary calcination]
[0200] (Crystal (2-3)) was obtained in the same manner as in Example 1 except that Crystal (2-2) was used instead of Crystal (1-2).
[0201] [Example 3]
[0202] [Preparation of Crystal (A3)]
[0203] The crystal (A3) having an MSE framework was prepared by the following method.
[0204] First, 15.62 g of (8 mol / L) NaOH aqueous solution, 16.22 g of (8 mol / L) KOH aqueous solution, 40.60 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 67.20 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content: 40 mass %)) are placed in a container and stirred at 80°C to obtain a sol-like substance.
[0205] Then, 13.56 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) was added to the obtained sol-like substance and mixed. The stirring time was adjusted so that the HMR value at this stage became 4.00. Then, the mixture was placed in an autoclave and heated at 165°C for 40 hours. The cooled mixture was filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (A3). The highest diffraction peak measured by XRD was observed at 21.66°.
[0206] [First step: preparation of aluminosilicate]
[0207] Next, 7.81 g of (8 mol / L) NaOH aqueous solution, 8.14 g of (8 mol / L) KOH aqueous solution, 24.39 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 36.14 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content is 40 mass%)) are placed in a container, stirred at 80°C to obtain a sol-like substance, and 0.79 g of the above-mentioned crystals (A3) and 6.78 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) are added and mixed. The stirring time is adjusted so that the HMR value at this stage becomes 5.50. Then, the mixture is placed in an autoclave and heated at 160°C for 50 hours. Then, the cooled mixture is filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (3-0).
[0208] The highest peak in the 17.5-35° region of the crystal (3-0) measured by XRD was observed at 21.64°, and the intensity ratio of the peak observed at 26.14° as the highest peak in the 25.0-27.0° region was 4.125. The XRD spectrum is as follows Figure 1 shown.
[0209] The above crystal (3-0) was calcined at 550°C for 10 hours to obtain a crystal (3-1).
[0210] [Second step: contact with acid, third step: primary calcination]
[0211] Crystal (3-2) was obtained in the same manner as in Example 1 except that Crystal (3-1) was used instead of Crystal (1-1).
[0212] [Fourth step: contact with titanium compound, secondary calcination]
[0213] (Crystal (3-3)) was obtained in the same manner as in Example 1 except that Crystal (3-2) was used instead of Crystal (1-2).
[0214] [Comparative Example]
[0215] [Preparation of Crystal (A-c1)]
[0216] Crystal (A-c1) was obtained by the same method as in the preparation of Crystal (A1) of Example 1.
[0217] [Preparation of Aluminosilicate]
[0218] Next, 7.81 g of (8 mol / L) NaOH aqueous solution, 8.11 g of (8 mol / L) KOH aqueous solution, 20.30 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 32.68 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content is 40 mass%)) were placed in a container, stirred at 80°C, and then continued to stir for a longer time than in Example 1, thereby dehydrating to HMR = 3.50. At this time, the mixture was in a solidified block state, and it was judged that it needed to be crushed in order to react with zeolite and the like in the next step. Therefore, 0.79 g of the above-mentioned crystal (A-c1) and 6.78 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) were added to the raw material mixture, crushed with a mortar, and after being fully mixed, the mixture was charged into an autoclave and heated at 160°C for 55 hours. Then, the cooled mixture was filtered, washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (C1-0).
[0219] The highest peak in the 17.5-35° region of the crystal (C1-0) measured by XRD was observed at 21.58°, and the intensity ratio of the peak observed at 25.72° as the highest peak in the 25.0-27.0° region was 1.54. The XRD spectrum is as follows Figure 1 shown.
[0220] The above crystal (C1-0) was calcined at 550°C for 10 hours to obtain a crystal (C1-1).
[0221] [Contact with acid, primary firing]
[0222] Crystal (C1-2) was obtained in the same manner as in Example 1 except that Crystal (C1-1) was used instead of Crystal (1-1).
[0223] [Contact with titanium compound, secondary firing]
[0224] Crystal (C1-3) was obtained in the same manner as in Example 1 except that Crystal (C1-2) was used instead of Crystal (1-2).
[0225] [Example 4]
[0226] [First step: preparation of aluminosilicate]
[0227] 7.81 g (8 mol / L) of NaOH aqueous solution, 8.09 g (8 mol / L) of KOH aqueous solution, 20.3 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 31.8 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content is 40 mass%)) are placed in a container, stirred at 80°C to obtain a sol-like substance, and 6.78 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) is added and mixed. The stirring time is adjusted so that the HMR value at this stage becomes 4.00. The contents are heated at 165°C for 40 hours using the same autoclave as above. Then, the cooled mixture is filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (4-0).
[0228] The highest peak in the 17.5-35° region of the crystal (4-0) measured by XRD was observed at 21.6°, and the intensity ratio of the peak observed at 25.78° as the highest peak in the 25.0-27.0° region was 4.39. The XRD spectrum is as follows Figure 2 The above crystal (4-0) was calcined at 550°C for 10 hours to obtain a crystal (4-1).
[0229] [Second step: contact with acid, third step: primary calcination]
[0230] 2 g of the above-prepared crystal (4-1) and 80 g of 65% nitric acid were added to a container and mixed, and the mixture was placed in an autoclave and heated at 148°C for 24 hours. The cooled mixture was filtered and washed with water, air-dried for 1 day, and then calcined at 600°C for 2 hours to obtain crystal (4-2).
[0231] [Fourth step: contact with titanium compound, secondary calcination]
[0232] 1 g of the above-prepared crystal (4-2) and 5 g of a titanium tetrachloride aqueous solution with a Ti concentration of 16% were placed in a container and heated and stirred at 40°C for 1 hour using an oil bath. Water was then added for filtration and further washing, and the dried product was subjected to secondary calcination at 650°C for 2 hours to obtain a crystalline porous aluminum titanium silicate (crystal (4-3)). The A
[300] of the above crystal (4-3) was 0.755, the A
[210] was 2.873, and the value of A
[300] / A
[210] was 0.246.
[0233] [Example 5]
[0234] In the first step, 31.94 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content of 40 mass%)) was used, the stirring time was adjusted so that the HMR value became 5.00, and the contents were heated at 150° C. for 100 hours using an autoclave. Except for this, the same operation as in Example 4 was performed to obtain crystal (5-0), crystal (5-1), crystal (5-2) and crystalline porous aluminum titanosilicate (crystal (5-3)). The XRD spectrum of the crystal (5-0) is as follows: Figure 2 The A
[300] of the crystal (5-3) is 0.083, the A
[210] is 1.676, and the value of A
[300] / A
[210] is 0.050.
[0235] [Example 6]
[0236] In the first step, 31.8 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content: 40 mass %)) was used, the stirring time was adjusted so that the HMR value was 5.00, and the contents were heated at 150° C. for 120 hours using an autoclave. Except for this, the same operation as in Example 4 was performed to obtain crystal (6-0), crystal (6-1), crystal (6-2) and crystalline porous aluminum titanosilicate (crystal (6-3)). The XRD spectrum of the crystal (6-0) is as follows: Figure 2 The A
[300] of the crystal (6-3) is 0.131, the A
[210] is 1.975, and the value of A
[300] / A
[210] is 0.066.
[0237] [Example 7]
[0238] [Preparation of Crystal (A7)]
[0239] The crystal (A7) having an MSE framework was prepared by the following method.
[0240] First, 15.62 g of (8 mol / L) NaOH aqueous solution, 16.24 g of (8 mol / L) KOH aqueous solution, 40.60 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 67.23 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content: 40 mass %)) are placed in a container and stirred at 80°C to obtain a sol-like substance.
[0241] Then, 13.56 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) was added to the obtained sol-like substance and mixed. The stirring time was adjusted so that the HMR value at this stage became 4.00. Then, the mixture was placed in an autoclave and heated at 165°C for 40 hours. The cooled mixture was filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (A7). The highest diffraction peak determined by XRD was observed at 21.58°.
[0242] [First step: preparation of aluminosilicate]
[0243] Next, 7.82 g of (8 mol / L) NaOH aqueous solution, 8.17 g of (8 mol / L) KOH aqueous solution, 24.36 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 35.38 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich Co. (SiO2 content: 40 mass %)) were placed in a container and stirred at 80°C to obtain a sol-like substance, and 0.79 g of the above-mentioned crystals (A7) and 6.79 g of FAU-type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) were added and mixed.
[0244] The stirring time was adjusted so that the HMR value at this stage was 6.50. The mixture was then placed in an autoclave and heated at 150°C for 68 hours. The cooled mixture was then filtered, washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (7-0).
[0245] The highest peak in the 17.5-35° region of the crystal (7-0) measured by XRD was observed at 21.58°, and the intensity ratio of the peak observed at 26.08° as the highest peak in the 25.0-27.0° region was 4.490. The XRD spectrum is as follows Figure 2 The above crystal (7-0) was calcined at 550°C for 10 hours to obtain a crystal (7-1).
[0246] [Second step: contact with acid, third step: primary calcination]
[0247] Crystal (7-2) was obtained in the same manner as in Example 1 except that Crystal (7-1) was used instead of Crystal (1-1).
[0248] [Fourth step: contact with titanium compound, secondary calcination]
[0249] Crystal (7-3) was obtained in the same manner as in Example 1 except that Crystal (7-2) was used instead of Crystal (1-2). Crystal (7-3) had an A
[300] of 0.102, an A
[210] of 2.215, and an A
[300] / A
[210] value of 0.046.
[0250] [Example 8]
[0251] [First step: preparation of aluminosilicate]
[0252] 7.81 g (8 mol / L) of NaOH aqueous solution, 8.11 g (8 mol / L) of KOH aqueous solution, 20.35 g of 40 wt% dimethyldipropylammonium hydroxide aqueous solution and 33.57 g of colloidal silica (product name: LUDOX (registered trademark) AS-40, manufactured by Sigma Aldrich (SiO2 content of 40 mass%)) were placed in a container, stirred at 80°C to obtain a sol-like substance, and 6.78 g of FAU type zeolite (product name: HSZ-HUA350, manufactured by Tosoh Corporation) was added and mixed. The stirring time was adjusted so that the HMR value at this stage became 4.00. The contents were heated at 150°C for 90 hours using the same autoclave as above. Then, the cooled mixture was filtered and washed with water, and vacuum dried at 70°C for 2 hours to obtain crystals (8-0).
[0253] The highest peak in the 17.5-35° region of the crystal (8-0) measured by XRD was observed at 21.64°, and the intensity ratio of the peak observed at 25.76° as the highest peak in the 25.0-27.0° region was 3.54. The XRD spectrum is as follows Figure 2 The above crystal (8-0) was calcined at 550°C for 10 hours to obtain a crystal (8-1).
[0254] [Second step: contact with acid, third step: primary calcination]
[0255] Crystal (8-2) was obtained in the same manner as in Example 4 except that Crystal (8-1) was used instead of Crystal (4-1).
[0256] [Fourth step: contact with titanium compound, secondary calcination]
[0257] Crystal (8-3) was obtained in the same manner as in Example 5 except that Crystal (8-2) was used instead of Crystal (4-2). Crystal (8-3) had an A
[300] of 0.086, an A
[210] of 1.682, and an A
[300] / A
[210] value of 0.051.
[0258] [Evaluation of performance as catalyst]
[0259] Next, the performance of the crystalline porous aluminum titanosilicates of Examples 1 to 8 and Comparative Example 1 as catalysts for producing hydroquinone was evaluated. The results are summarized in Tables 1 and 2. In the tables, HQ represents hydroquinone and CL represents catechol. The measurement method and calculation formulas for each value are shown below.
[0260] [Measurement method]
[0261] In a 50 ml flask equipped with a condenser, a thermometer, a feed pump and a magnetic stirring piece, 0.2 g of each catalyst, 4.2 g of phenol, 3.0 g of tert-butyl alcohol, and 6.0 g of water were added, and heated to 50° C. in a hot water bath while stirring with a stirrer. Here, 0.5 g of 34% hydrogen peroxide was added dropwise from the feed pump over 10 minutes, and the state was maintained for 60 minutes. After cooling the reaction liquid, the catalyst was filtered out, and a portion of the reaction liquid was taken to quantify the product by gas chromatography.
[0262] The analysis conditions of gas chromatography were as follows.
[0263] Detector: Hydrogen flame ionization detector
[0264] ·Chromatographic column: DB-5 (Agilent J&W), inner diameter 0.25 mm, length 60 m, film thickness 0.25 μm
[0265] Column temperature: maintain at 50°C for 10 minutes, then increase the temperature by 10°C / min to 280°C
[0266] Inlet: 280℃
[0267] Detector temperature: 280℃
[0268] Carrier gas: Helium
[0269] Flow rate: 80ml / min
[0270] (Calculation formula)
[0271] The yield of hydroquinone was determined by calculation using the following formula.
[0272] Hydroquinone yield (%) = (hydrogen peroxide utilization efficiency) × (number of moles of hydroquinone produced) / [(number of moles of hydroquinone produced) + (number of moles of catechol produced)] × 100
[0273] Hydroquinone / catechol ratio = (number of moles of hydroquinone produced) / (number of moles of catechol produced)
[0274] Table 1
[0275]
[0276] Table 2
[0277]
[0278] As can be seen from Tables 1 and 2, the aluminum titanosilicate prepared by the method for producing a modified aluminum silicate that satisfies the above-mentioned requirement of [1] of the present invention shows a high hydroquinone yield and a high hydroquinone selectivity. In addition, since sol-like silica can be used in the middle, the modified aluminum silicate can be produced by an industrially advantageous method.
[0279] Furthermore, it can be seen that the use of modified aluminosilicates showing a specific [A300] / [A210] range shows very high HQ yields.
Claims
1. A method for producing a modified aluminosilicate, comprising the following steps: The first step is to prepare a liquid in which a sol-like silica containing water is brought into contact with a metal compound AL containing aluminum and oxygen, thereby obtaining an aluminosilicate in which the molar ratio HMR of water to silica, i.e., H2O / SiO2, in the liquid is in the range of 0.1 to 8.0; The second step is to treat the aluminosilicate obtained in the first step with an acid; The third step is to calcine the treated product obtained in the second step at 550° C. to 850° C.; as well as The fourth step is to bring the fired product obtained in the third step into contact with a liquid containing one or more elements selected from the group consisting of Group 4 elements and Group 5 elements of the periodic table, and then dry and perform secondary firing.
2. The method for producing a modified aluminosilicate according to claim 1, wherein: The HMR is in the range of 3.0 to 6.
6.
3. The method for producing a modified aluminosilicate according to claim 1, wherein: The metal compound AL containing aluminum and oxygen is zeolite.
4. The method for producing a modified aluminosilicate according to claim 1, wherein: The first step includes a step of removing a portion of water.
5. The method for producing a modified aluminosilicate according to claim 1, wherein: In the first step, after preparing a liquid in which sol-state silica containing water is brought into contact with zeolite, a portion of the water in the liquid is removed to obtain an aluminosilicate having a molar ratio HMR of water to silica, i.e., H2O / SiO2, in the range of 0.1 to 8.
0.
6. A method for producing a catalyst for producing an aromatic polyhydroxy compound, the catalyst comprising the modified aluminosilicate according to claim 1.
7. A method for producing a catalyst for producing an aromatic polyhydroxy compound, the catalyst comprising the modified aluminosilicate according to claim 5.
8. A method for producing an aromatic polyhydroxy compound, comprising: A step of reacting an aromatic hydroxy compound with hydrogen peroxide in the presence of the catalyst according to claim 6.
9. A method for producing an aromatic polyhydroxy compound, comprising: A step of reacting an aromatic hydroxy compound with hydrogen peroxide in the presence of the catalyst according to claim 7.
10. A modified aluminosilicate, wherein the ratio of the absorbance A[300] at 300 nm in the ultraviolet-visible absorption spectrum to the absorbance [210] at 210 nm in the ultraviolet-visible absorption spectrum, i.e. A[300] / A[210], is 0.045 or more and 0.070 or less.
